Correction: Müller et al. Henneguya correai n. sp. (Cnidaria, Myxozoa) Parasitizing the Fins of the Amazonian Fish Semaprochilodus insignis. Diversity 2023, 15, 702 - Maria I. Müller; Rayline T. A. Figueredo; Stephen D. Atkinson; Jerri L. Bartholomew; Edson A. Adriano (Diversity)
In the published publication [...]